Cuvântul rostit de actor: Idei care emoționează - Mihăilă, Cătălina-Elena (Theatrical Research, 2021)
The word spoken by the actor on stage can be caught beyond the beauty, clarity, precision of the soundtrack. We thus discover its deepness, the essence of the logos that convey ideas and emotions. Therefore, it cuts the verbal instrument's thought and soul and forms a connection between the inner universes belonging to the artist and the spectator. We are talking about a word born from a necessity and which acquires the quality of being organic, invading the inside of the receiver.